Northern Bobwhite Demographic and Population Response Following an Intensive Habitat Modification to an Agricultural Landscape - Theron M. Terhune; D. Clay Sisson; Steven Mitchell; H. Lee Stribling (National Quail Symposium Proceedings, 2017)
Northern Bobwhite (Colinus virginianus) populations have been declining throughout most of their endemic range due to numerous factors (e.g., increased urbanization, predators); however, changing land-use practices have proved most detrimental to bobwhites. In parts of the southeastern USA, small-scale farming has been replaced by large-scale center-pivot irrigated fields and this has exacerbated habitat loss. Despite these trends, bobwhite populations in the Southeast have remained stable or increased on many areas employing intensive habitat management regimes, substantiating the importance of appropriate habitat management for long-term bobwhite persistence. In effort to reverse one such decline, we intensively modified a center-pivot, agriculture dominated landscape to benefit bobwhites by creating new habitat and improving existing habitat. Techniques utilized to modify this landscape were: establishment of linear habitats (field borders and buffer strips); planting longleaf pines; and management of existing habitat via prescribed burning and timber management. During 1998-2001, we monitored bobwhite (n = 498) demographics and population response following annual habitat restoration and management using radio-telemetry and fall abundance estimation (i.e., covey call-counts). Average survival during over-winter (0.4698, SE = 0.0721), breeding (0.3561, SE = 0 .0667) and annual (0.1673, SE = 0.0411) time-periods were higher than those reported for other agriculture studies and similar to those of intensively managed, “plantation” habitats. Bobwhite coveys and broods used newly developed longleaf pine, linear habitats (e.g. field borders/hedgerows), and managed woodlands. Further, nest site selection was commonly associated with these novel habitat types. As a result of the positive demographic response to habitat modification, bobwhite abundance also improved during the study. Consequently, we surmised that modification of agricultural landscapes may improve habitat quality and quantity for bobwhites and subsequently help to increase demographic rates and bobwhite abundance.
Keywords: agriculture; buffer strips; field borders; habitat use; home range; northern bobwhite; PROC NLMIXED; Program MARK; reproduction; SAS; survival